A photovoltaic panel surface coating material with low-temperature curing, antistatic and anti-reflection properties

By using anti-reflection coating solution, combined with hollow silica nanoparticles and solid zirconium dioxide nanoparticles, the low-temperature curing, anti-static and anti-reflection characteristics of the photovoltaic panel surface coating are achieved, solving the problems of high energy consumption and insufficient performance in the prior art, and improving the performance and market value of photovoltaic panels.

CN119735973APending Publication Date: 2025-04-01SHANXI RISHENGDA SOLAR TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510017376.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing photovoltaic panel surface coating consumes a high energy consumption during high-temperature curing, and cannot meet the anti-static, anti-reflective characteristics and low-temperature curing properties at the same time.

Method used

An anti-reflective coating solution is used, which includes hollow silica nanoparticles, solid zirconium dioxide nanoparticles, silica sol, water, ethanol and isopropanol, and a coating with low-temperature curing, anti-static and anti-reflective properties is formed by mixing room temperature and curing at low temperature.

Benefits of technology

It achieves the reduction of energy consumption during low-temperature curing, and has excellent anti-reflection effect and anti-static characteristics, which improves the light transmittance of photovoltaic panels and the added value of the product.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a photovoltaic panel surface coating material with low-temperature curing, antistatic and anti-reflection properties, which belongs to the field of photovoltaic panel maintenance technology, and solves the technical problems that the existing photovoltaic panel surface coating has high energy consumption and cannot simultaneously meet the antistatic, anti-reflection properties and low-temperature curing performance. The solution is: an anti-reflection coating solution, comprising the following components by weight: 8-15 parts of hollow silica nanoparticles, 2-10 parts of conductive particles, 5-10 parts of film-forming agent, 30-40 parts of water, 15-20 parts of leveling agent, and 25-35 parts of coating diluent. A method for preparing an anti-reflection coating solution, comprising the following steps: 1) mixing and stirring each composition in proportion at room temperature for 24 hours; 2) stirring for 24 hours and then stirring in a closed water bath environment at 60-65°C for 48 hours to cool to room temperature. Compared with the prior art, the present invention has the advantages of low energy consumption, being able to simultaneously meet the antistatic, anti-reflection properties and low-temperature curing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photovoltaic panel maintenance, and specifically relates to a photovoltaic panel surface coating material with low-temperature curing, antistatic and anti-reflection properties. Background Art

[0002] The construction and operation of solar photovoltaic power stations have entered a peak period. At the same time, the reduced power generation efficiency of solar photovoltaic panels due to surface pollution has become a difficult problem that needs to be solved. When solar panels are placed outdoors, a large amount of sand, coal ash, carbon ash, pollen, bird droppings and even oil will accumulate on the surface, reducing the power generation rate by an average of 5%-29%. In order to maintain the power generation efficiency of photovoltaic panels, power stations generally use various means such as robot cleaning and manual cleaning. Manual cleaning is not ideal in places with high winds, sand and rain. In addition, these cleaning methods will not only incur high cleaning costs while improving power generation efficiency, but may also cause damage to photovoltaic modules.

[0003] Currently, a coating has been constructed on the surface of solar photovoltaic panels. However, the existing surface coatings are all calcined at high temperatures to volatilize the wrapped resin to form gaps to achieve the effect of increasing transmittance, which has high energy consumption and cannot simultaneously meet the requirements of anti-static, anti-reflection properties and low-temperature curing performance. Summary of the invention

[0004] In order to overcome the shortcomings of the prior art and solve the technical problems that the existing photovoltaic panel surface coating has high energy consumption and cannot simultaneously meet the anti-static, anti-reflection properties and low-temperature curing performance, the present invention provides a photovoltaic panel surface coating material with low-temperature curing, anti-static and anti-reflection properties.

[0005] The present invention is achieved through the following technical solutions.

[0006] The invention provides an anti-reflection coating solution, comprising the following components in parts by weight: 8-15 parts of hollow silica nanoparticles, 2-10 parts of conductive particles, 5-10 parts of film-forming agent, 30-40 parts of water, 15-20 parts of leveling agent, and 25-35 parts of coating diluent.

[0007] Furthermore, the particle size of the hollow silica nanoparticles is 40-100 nm.

[0008] Furthermore, the conductive particles are solid zirconium dioxide nanoparticles.

[0009] Furthermore, the film-forming agent is silica sol, and the solid content of the silica sol is 40%.

[0010] Furthermore, the leveling agent is ethanol, and the coating diluent is isopropanol.

[0011] Furthermore, a method for preparing an anti-reflection coating solution comprises the following steps:

[0012] 1) 8-15 parts of hollow silica nanoparticles, 2-10 parts of solid zirconium dioxide nanoparticles, 5-10 parts of silica sol, 30-40 parts of water, 15-20 parts of ethanol and 25-35 parts of isopropanol were mixed and stirred at room temperature for 24 hours;

[0013] 2) After stirring for 24 hours, the mixture was stirred in a closed environment at 60-65° C. for 48 hours and then cooled to room temperature to obtain an anti-reflection coating solution.

[0014] Furthermore, the photovoltaic panel surface coating material with low-temperature curing, antistatic and anti-reflection properties is prepared from an anti-reflection coating solution.

[0015] Furthermore, a photovoltaic glass comprises a glass substrate and a coating layer coated on the glass substrate by a roller, wherein the coating layer is formed by an anti-reflection coating solution.

[0016] Furthermore, the glass substrate is ultra-white embossed glass, one side of the glass substrate is an embossed surface, and the other side is a velvet surface, and the coating layer is formed on the velvet surface.

[0017] Furthermore, a method for preparing photovoltaic glass comprises the following steps:

[0018] 1) performing edge grinding, cleaning and drying pretreatment on the glass substrate;

[0019] II) heat treating the glass substrate obtained in step I) at 30-60° C. for 0.5-1 min;

[0020] III) coating the glass substrate obtained by the treatment in step II) with an anti-reflection coating solution to form a coating layer;

[0021] IV) Curing the glass substrate obtained in step III) at room temperature for 24 hours to obtain photovoltaic glass.

[0022] The beneficial effects achieved by the present invention are as follows: the present invention uses an anti-reflection coating solution, the anti-reflection coating solution includes hollow silica nanoparticles, the hollow silica nanoparticles are not only hydrophilic, but also enable the anti-reflection coating solution to form a coating with a porous structure after low-temperature curing, thereby reducing the refractive index of the coating, so that it has an excellent anti-reflection effect, which is different from traditional high-temperature curing and reduces energy consumption; the anti-reflection coating solution also includes solid zirconium dioxide nanoparticles, so that the coating layer has antistatic properties; the photovoltaic panel surface coating material with low-temperature curing, antistatic and anti-reflection properties prepared by using the anti-reflection coating solution can have a light transmittance of 93.95%-94.23%, thereby improving the added value of the product and having very good market value and application prospects.

[0023] Compared with the prior art, the present invention has the advantages of low energy consumption, being able to simultaneously meet the requirements of antistatic and anti-reflection properties and low-temperature curing, etc. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below in conjunction with embodiments.

[0025] Example 1

[0026] An anti-reflection coating solution comprises the following components by weight: 8g of hollow silica nanoparticles, 2g of conductive particles, 5g of film-forming agent, 30g of water, 15g of leveling agent, and 25g of coating diluent, wherein the hollow silica nanoparticles have a particle size of 40-100nm, the hollow silica nanoparticles not only have hydrophilicity, but also can form a coating with a porous structure after low-temperature curing of the anti-reflection coating solution, thereby reducing the refractive index of the coating, so that it has an excellent anti-reflection effect, which is different from the traditional high-temperature curing and reduces energy consumption. The conductive particles are solid zirconium dioxide nanoparticles, and the solid zirconium dioxide nanoparticles have antistatic properties. The film-forming agent is silica sol, and the solid content of the silica sol is 40%. The leveling agent is ethanol, which can reduce the surface tension of the anti-reflection coating solution and form a flat, smooth and uniform coating layer during the drying process. The coating diluent is isopropanol, and the viscosity is adjusted to meet actual needs.

[0027] A method for preparing an anti-reflection coating solution comprises the following steps:

[0028] 1) 8 g of hollow silica nanoparticles, 2 g of solid zirconium dioxide nanoparticles, 5 g of silica sol, 30 g of water, 15 g of ethanol and 25 g of isopropanol were mixed and stirred at room temperature for 24 h;

[0029] 2) After stirring for 24 hours, the mixture was stirred in a sealed environment at 60° C. for 48 hours and then cooled to room temperature to obtain an anti-reflection coating solution.

[0030] The photovoltaic panel surface coating material with low-temperature curing, antistatic and anti-reflection properties is prepared from an anti-reflection coating solution, so that it has low-temperature curing, antistatic and anti-reflection properties at the same time.

[0031] A photovoltaic glass comprises a glass substrate and a coating layer coated on the glass substrate by a roller, wherein the coating layer is formed by an anti-reflection coating solution. The glass substrate is ultra-white embossed glass, one side of the glass substrate is an embossed surface, and the other side is a velvet surface, and the coating layer is formed on the velvet surface.

[0032] A method for preparing photovoltaic glass comprises the following steps:

[0033] 1) performing edge grinding, cleaning and drying pretreatment on the glass substrate to remove impurities and moisture from the glass substrate;

[0034] II) heat treating the glass substrate obtained in step I) at 30° C. for 0.5 min, so as to remove the residual moisture in the glass substrate;

[0035] III) coating the glass substrate obtained by the treatment in step II) with an anti-reflection coating solution to form a coating layer;

[0036] IV) curing the glass substrate obtained in step III) at room temperature for 24 hours to obtain photovoltaic glass, and controlling the uniformity of the glass substrate to remain unchanged.

[0037] The final photovoltaic glass was tested and found to have a light transmittance of 94.23% and a surface resistivity of 9.4*10 7 Ω·m, the water drop angle is 3°.

[0038] Example 2

[0039] An anti-reflection coating solution comprises the following components in parts by weight: 10g of hollow silica nanoparticles, 7g of conductive particles, 7g of film-forming agent, 35g of water, 17g of leveling agent, and 30g of coating diluent, wherein the hollow silica nanoparticles have a particle size of 40-100nm, the hollow silica nanoparticles not only have hydrophilicity, but also enable the anti-reflection coating solution to form a coating with a porous structure after low-temperature curing, thereby reducing the refractive index of the coating, so that it has an excellent anti-reflection effect, which is different from the traditional high-temperature curing and reduces energy consumption. The conductive particles are solid zirconium dioxide nanoparticles, and the solid zirconium dioxide nanoparticles have antistatic properties. The film-forming agent is silica sol, and the solid content of the silica sol is 40%. The leveling agent is ethanol, which can reduce the surface tension of the anti-reflection coating solution and form a flat, smooth and uniform coating layer during the drying process. The coating diluent is isopropanol, and the viscosity is adjusted to meet actual needs.

[0040] A method for preparing an anti-reflection coating solution comprises the following steps:

[0041] 1) 10 g of hollow silica nanoparticles, 7 g of solid zirconium dioxide nanoparticles, 7 g of silica sol, 35 g of water, 17 g of ethanol and 30 g of isopropanol were mixed and stirred at room temperature for 24 h;

[0042] 2) After stirring for 24 hours, the mixture was stirred in a closed environment at 63° C. for 48 hours and then cooled to room temperature to obtain an anti-reflection coating solution.

[0043] The photovoltaic panel surface coating material with low-temperature curing, antistatic and anti-reflection properties is prepared from an anti-reflection coating solution, so that it has low-temperature curing, antistatic and anti-reflection properties at the same time.

[0044] A photovoltaic glass comprises a glass substrate and a coating layer coated on the glass substrate by a roller, wherein the coating layer is formed by an anti-reflection coating solution. The glass substrate is ultra-white embossed glass, one side of the glass substrate is an embossed surface, and the other side is a velvet surface, and the coating layer is formed on the velvet surface.

[0045] A method for preparing photovoltaic glass comprises the following steps:

[0046] 1) performing edge grinding, cleaning and drying pretreatment on the glass substrate to remove impurities and moisture from the glass substrate;

[0047] II) heat-treating the glass substrate obtained in step I) at 45° C. for 1 min, so as to remove the residual moisture in the glass substrate;

[0048] III) coating the glass substrate obtained by the treatment in step II) with an anti-reflection coating solution to form a coating layer;

[0049] IV) curing the glass substrate obtained in step III) at room temperature for 24 hours to obtain photovoltaic glass, and controlling the uniformity of the glass substrate to remain unchanged.

[0050] The final photovoltaic glass was tested and found to have a light transmittance of 94.20% and a surface resistivity of 7.8*10 7 Ω·m, the water drop angle is 5°.

[0051] Example 3

[0052] An anti-reflection coating solution comprises the following components in parts by weight: 15g of hollow silica nanoparticles, 10g of conductive particles, 10g of film-forming agent, 40g of water, 20g of leveling agent, and 35g of coating diluent, wherein the hollow silica nanoparticles have a particle size of 40-100nm, the hollow silica nanoparticles not only have hydrophilicity, but also can form a coating with a porous structure after low-temperature curing of the anti-reflection coating solution, thereby reducing the refractive index of the coating, so that it has an excellent anti-reflection effect, which is different from the traditional high-temperature curing and reduces energy consumption. The conductive particles are solid zirconium dioxide nanoparticles, and the solid zirconium dioxide nanoparticles have antistatic properties. The film-forming agent is silica sol, and the solid content of the silica sol is 40%. The leveling agent is ethanol, which can reduce the surface tension of the anti-reflection coating solution and form a flat, smooth and uniform coating layer during the drying process. The coating diluent is isopropanol, and the viscosity is adjusted to meet actual needs.

[0053] A method for preparing an anti-reflection coating solution comprises the following steps:

[0054] 1) 15 g of hollow silica nanoparticles, 10 g of solid zirconium dioxide nanoparticles, 10 g of silica sol, 40 g of water, 20 g of ethanol and 35 g of isopropanol were mixed and stirred at room temperature for 24 h;

[0055] 2) After stirring for 24 hours, the mixture was stirred in a closed environment at 65° C. for 48 hours and then cooled to room temperature to obtain an anti-reflection coating solution.

[0056] The photovoltaic panel surface coating material with low-temperature curing, antistatic and anti-reflection properties is prepared from an anti-reflection coating solution, so that it has low-temperature curing, antistatic and anti-reflection properties at the same time.

[0057] A photovoltaic glass comprises a glass substrate and a coating layer coated on the glass substrate by a roller, wherein the coating layer is formed by an anti-reflection coating solution. The glass substrate is ultra-white embossed glass, one side of the glass substrate is an embossed surface, and the other side is a velvet surface, and the coating layer is formed on the velvet surface.

[0058] A method for preparing photovoltaic glass comprises the following steps:

[0059] 1) performing edge grinding, cleaning and drying pretreatment on the glass substrate to remove impurities and moisture from the glass substrate;

[0060] II) heat treating the glass substrate obtained in step I) at 60° C. for 1 min, so as to remove the residual moisture in the glass substrate;

[0061] III) coating the glass substrate obtained by the treatment in step II) with an anti-reflection coating solution to form a coating layer;

[0062] IV) curing the glass substrate obtained in step III) at room temperature for 24 hours to obtain photovoltaic glass, and controlling the uniformity of the glass substrate to remain unchanged.

[0063] The final photovoltaic glass was tested and found to have a light transmittance of 94.05% and a surface resistivity of 5.3*10 7 Ω·m, the water drop angle is 8°.

[0064] The above describes in detail the implementation modes of the present invention, but the present invention is not limited to the above implementation modes. The implementation modes can still be changed within the knowledge scope of ordinary technicians in the field. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An anti-reflection coating solution, characterized in that: The invention comprises the following components in parts by weight: 8-15 parts of hollow silicon dioxide nanoparticles, 2-10 parts of conductive particles, 5-10 parts of film-forming agent, 30-40 parts of water, 15-20 parts of leveling agent and 25-35 parts of coating diluent.

2. The anti-reflection coating solution according to claim 1, characterized in that: The particle size of the hollow silica nanoparticles is 40-100 nm.

3. The anti-reflection coating solution according to claim 1, characterized in that: The conductive particles are solid zirconium dioxide nanoparticles.

4. The anti-reflection coating solution according to claim 1, characterized in that: The film-forming agent is silica sol, and the solid content of the silica sol is 40%.

5. The anti-reflection coating solution according to claim 1, characterized in that: The leveling agent is ethanol, and the coating diluent is isopropanol.

6. A method for preparing an anti-reflection coating solution according to any one of claims 1 to 5, characterized in that: The steps include: 1) 8-15 parts of hollow silica nanoparticles, 2-10 parts of solid zirconium dioxide nanoparticles, 5-10 parts of silica sol, 30-40 parts of water, 15-20 parts of ethanol and 25-35 parts of isopropanol were mixed and stirred at room temperature for 24 hours; 2) After stirring for 24 hours, the mixture was stirred in a closed environment at 60-65° C. for 48 hours and then cooled to room temperature to obtain an anti-reflection coating solution.

7. A photovoltaic panel surface coating material with low temperature curing, antistatic and anti-reflection properties, characterized in that: The photovoltaic panel surface coating material with low-temperature curing, antistatic and anti-reflection properties is prepared from the anti-reflection coating solution described in any one of claims 1-5.

8. A photovoltaic glass, characterized in that: The invention comprises a glass substrate and a coating layer which is roller-coated on the glass substrate, wherein the coating layer is formed by the anti-reflection coating solution according to any one of claims 1 to 5.

9. The photovoltaic glass according to claim 8, characterized in that: The glass substrate is ultra-white embossed glass, one side of the glass substrate is an embossed surface, and the other side is a velvet surface, and the coating layer is formed on the velvet surface.

10. A method for preparing the photovoltaic glass according to claim 9, characterized in that: The steps include: 1) performing edge grinding, cleaning and drying pretreatment on the glass substrate; II) heat treating the glass substrate obtained in step I) at 30-60° C. for 0.5-1 min; III) coating the glass substrate obtained by the treatment in step II) with an anti-reflection coating solution to form a coating layer; IV) Curing the glass substrate obtained in step III) at room temperature for 24 hours to obtain photovoltaic glass.